Statistik demografi Menochilus sexmaculatus (Fabricius) (Coleoptera: Coccinellidae) pada Aphis craccivora Koch (Hemiptera: Aphididae): Demographic statistic of Menochilus sexmaculatus (Fabricius) (Coleoptera: Coccinellidae) on Aphis craccivora Koch (Hemiptera: Aphididae) - Mayasari, Astrid; Winasa, I Wayan; Nurmansyah, Ali (Perhimpunan Entomologi Indonesia, 2024)
Information on demographic statistics of Menochilus sexmaculatus (Fabricius) on Aphis craccivora Koch is important for the development of more effective and environmentally friendly pest control strategies. The objective of this experiment was to determine the demographic statistics (survival, fecundity, growth rate, reproductive rate, length of life), biological and morphometric of M. sexmaculatus on A. craccivora prey. A total of 15 pairs of M. sexmaculatus adult obtained from broad bean fields in Situgede, Bogor were reared in cages containing 3 polybags of broad bean plants (infested with A. craccivora as food for adult). One hundred eggs (6 egg batches) were collected from the cages and reared in plastic containers (top diameter 6.7 cm, bottom diameter 4.9 cm, height 6.3 cm) per 1 egg batch. Larvae that emerge from the egg are separated individually into 1 container and reared until the adult produced eggs again and died. Mean values and standard deviations of 5 demographic statistical parameters were determined using the Jacknife method. Survival probability and paternity were presented as curves. M. sexmaculatus had a mean body size of 7.32 × 5.94 mm for males and 8.63 × 6.98 mm for females. M. sexmaculatus has potential as a control agent for the pest A. craccivora. This potential is supported by its high reproductive ability (R0 35.72 ± 1,10 individuals/female/generation and GRR 128.85 ± 3.02 individuals/generation), fast population growth rate (r 0.20 ± 0.002 individuals/female/day), T which is 18.16 ± 0.04 days.